2003
DOI: 10.2135/cropsci2003.1414
|View full text |Cite
|
Sign up to set email alerts
|

Stockpiled Annual Ryegrass for Winter Forage in the Lower Midwestern USA

Abstract: Pasture growth, and thus forage supply, fluctuates throughout the year because of variable growing condi-Livestock operations, particularly pasture-based dairies in the tions (Fales et al., 1993; Matches and Burns, 1995). This lower Midwest, are interested in stockpiling annual ryegrass (Lolium multiflorum Lam.) as a source of high-quality winter forage. Almost creates an uneven forage supply and an intermittent no information exists about stockpiling annual ryegrass in this region.failure of the pasture syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
(26 reference statements)
3
16
3
Order By: Relevance
“…Cultivation of annual ryegrass in the Southeast accounts for 1.1 million hectares annually (Evers, 1995). The main use of annual ryegrass is for production of high nutritive value forage for stocker cattle, replacement heifer and lactating dairy cows during the winter and spring seasons (Balasko et al, 1995;Kallenbach et al, 2003;Lippke et al, 2006).…”
Section: Annual Ryegrassmentioning
confidence: 99%
“…Cultivation of annual ryegrass in the Southeast accounts for 1.1 million hectares annually (Evers, 1995). The main use of annual ryegrass is for production of high nutritive value forage for stocker cattle, replacement heifer and lactating dairy cows during the winter and spring seasons (Balasko et al, 1995;Kallenbach et al, 2003;Lippke et al, 2006).…”
Section: Annual Ryegrassmentioning
confidence: 99%
“…Although the seeding rate for the annual ryegrass/cereal rye was the same for both years, apparently the environmental conditions were more conducive to cereal rye in 2001 than in 2002. Kallenbach et al (2003) reported that the growth of cereal rye in the lower Midwestern USA was often variable between years and that the variability in growth depended largely on autumn temperature and rainfall.…”
Section: Forage Qualitymentioning
confidence: 99%
“…and cereal rye (Secale cereale L.) have become popular for late winter and spring grazing in the lower Midwest (Altom et al 1996). Producers establish this forage mix in late summer and then allow it to accumulate growth for deferred or 'stockpile' grazing in the late-winter (Kallenbach et al 2003). After the stockpiled forage is grazed, grazing continues through spring as new growth is available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a winter cover crop could suppress winter annual weeds (9,13), which are becoming more of a problem in Roundup‐Ready soybean (2). Finally, annual ryegrass or cereal rye could provide a winter forage source for beef cattle and stocker calves as discussed by Kallenbach et al (5) and Moyer and Coffey (7). Although this last benefit seems like a natural option for mixed row‐crop/livestock operations, it has largely been ignored in cover‐crop research.…”
Section: Introductionmentioning
confidence: 99%